Milk thistle protective effect on liver and kidney of broiler chickens - Gharahveysi, Shahabodin (Agriculture and Natural Resources, 2019)
Milk thistle, Silybum marianum is a useful medicinal plant, whose extract has antioxidant properties. The protective effect of the milk thistle medicinal plant was studied on the liver and kidney of Ross broiler chickens. Milk thistle at three levels (0%, 0.3%, 3%) as well as cotrimoxazole at two levels (0 g/kg, 2 g/kg) were used in five replications. Blood metabolites were measured at age 42 d. Data were analyzed using a general linear model. The effect of milk thistle levels was significant (p < 0.05) on blood cholesterol. Cotrimoxazole had a highly significant (p < 0.01) effect on blood cholesterol. The effect of milk thistle levels was significant (p < 0.05) on the levels of uric acid and blood creatinine. The effect of milk thistle levels was highly significant (p < 0.01) on blood bilirubin. The difference in the mean levels of milk thistle and cotrimoxazole was significant (p < 0.05) for prothrombin time. The use of different levels of milk thistle reduced liver and kidney problems and modified the undesirable effects of cotrimoxazole. A level of 3% milk thistle had the most protective effect on the liver and kidney of broilers.